Cryptic Prophages Contribution for Campylobacter jejuni and Campylobacter coli Introgression - Tanoeiro, Luis (2022)
Campylobacter coli and C. jejuni, the causing agents of campylobacteriosis, are described to be undergoing introgression events, i.e., the transference of genetic material between different species, with some isolates sharing almost a quarter of its genome. The participation of phages in introgression events and consequent impact on host ecology and evolution remain elusive. Three distinct prophages, named C. jejuni integrated elements 1, 2, and 4 (CJIE1, CJIE2, and CJIE4), are described in C. jejuni. Here, we identified two unreported prophages, Campylobacter coli integrated elements 1 and 2 (CCIE1 and CCIE2 prophages), which are C. coli homologues of CJIE1 and CJIE2, respectively. No induction was achieved for both prophages. Conversely, induction assays on CJIE1 and CJIE2 point towards the inducibility of these prophages. CCIE2-, CJIE1-, and CJIE4-like prophages were identified in a Campylobacter spp. population of 840 genomes, and phylogenetic analysis revealed clustering in three major groups: CJIE1-CCIE1, CJIE2-CCIE2, and CJIE4, clearly segregating prophages from C. jejuni and C. coli, but not from human- and nonhuman-derived isolates, corroborating the flowing between animals and humans in the agricultural context. Punctual bacteriophage host-jumps were observed in the context of C. jejuni and C. coli, and although random chance cannot be fully discarded, these observations seem to implicate prophages in evolutionary introgression events that are modulating the hybridization of C. jejuni and C. coli species.